Development of a health economic model to evaluate the potential benefits of optimal serum potassium management in patients with heart failure. (2nd December 2018) - Bakhai, Ameet; Palaka, Eirini; Linde, Cecilia; Bennett, Hayley; Furuland, Hans; Qin, Lei; McEwan, Phil; Evans, Marc
Abstract: Aims: Patients with heart failure are at increased risk of hyperkalemia, particularly when treated with renin-angiotensin-aldosterone system inhibitor (RAASi) agents. This study developed a model to quantify the potential health and economic value associated with sustained potassium management and optimal RAASi therapy in heart failure patients. Materials and methods: A patient-level, fixed-time increment stochastic simulation model was designed to characterize the progression of heart failure through New York Heart Association functional classes, and predict associations between serum potassium levels, RAASi use, and consequent long-term outcomes. Following internal and external validation exercises, model analyses sought to quantify the health and economic benefits of optimizing both serum potassium levels and RAASi therapy in heart failure patients. Analyses were conducted using a UK payer perspective, independent of costs and utilities related to pharmacological potassium management. Results: Validation against multiple datasets demonstrated the predictive capability of the model. Compared to those who discontinued RAASi to manage serum potassium, patients with normokalemia and ongoing RAASi therapy benefited from longer life expectancy (+1.38 years), per-patient quality-adjusted life year gains (+0.53 QALYs), cost savings (£110), and associated net monetary benefit (£10, 679 at £20, 000 per QALY gained) over a lifetime horizon. The predicted value of sustained potassium management and ongoing RAASi treatment was largely driven by reduced mortality and hospitalization risks associated with optimal RAASi therapy. Limitations: Several modeling assumptions were made to account for a current paucity of published literature; however, ongoing refinement and validation of the model will ensure its continued accuracy as the clinical landscape of hyperkalemia evolves. Conclusions: Predictions generated by this novel modeling approach highlight the value of sustained potassium management to avoid hyperkalemia, enable RAASi therapy, and improve long-term health economic outcomes in patients with heart failure.